2004
DOI: 10.1007/s00535-004-1469-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum hepatocyte growth factor and survival in untreated hepatocellular carcinoma

Abstract: Patients with inoperable HCC had higher levels of serum HGF than the healthy controls, and serum HGF was negatively correlated with the survival time. Serum HGF levels of 1.0 ng/ml or more in HCC patients are suggestive of a grave prognosis, indicating that HGF plays important and active roles in the disease progression. The detailed mechanisms need to be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 25 publications
2
38
0
1
Order By: Relevance
“…In mouse models, HGF through activation of Met signaling pathway may promote carcinogenesis because of the presence of Met receptors on HCC cells. 13,34 In our study we have demonstrated elevated levels of both HGF and EGF in patients with HBV infection compared to healthy controls. We have not, however, investigated the source of EGF or HGF.…”
Section: Discussionsupporting
confidence: 49%
“…In mouse models, HGF through activation of Met signaling pathway may promote carcinogenesis because of the presence of Met receptors on HCC cells. 13,34 In our study we have demonstrated elevated levels of both HGF and EGF in patients with HBV infection compared to healthy controls. We have not, however, investigated the source of EGF or HGF.…”
Section: Discussionsupporting
confidence: 49%
“…Additionally, overexpression of MET is detected predominantly in poorly differentiated HCCs (Daveau et al, 2003). Although one study does not demonstrate a correlation of HGF expression levels with patient survival or clinicopathological parameters (Ueki et al, 1997), recently published data show that higher HGF serum levels negatively correlate with patient survival time (Vejchapipat et al, 2004) and positively correlate with tumor size (Yamagamim et al, 2002).…”
Section: Transforming Growth Factor B Signaling Axismentioning
confidence: 99%
“…Therefore, novel treatment strategies are urgently needed. HCC tissues express higher levels of HGF than dysplastic nodules (15), and high levels of plasma HGF in HCC patients indicate a grave prognosis, suggesting that HGF plays important and active roles in the progression of HCC (16).…”
Section: Introductionmentioning
confidence: 99%